2016
DOI: 10.3390/molecules21091130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Flavone and Tyrosinase Inhibition Constituents from the Twigs of Morus alba L.

Abstract: Abstract:The twigs of Morus alba L. were found to show strong tyrosinase inhibition activity, and the responsible active components in the extract were further investigated in this study. A flavone, named morusone (1), and sixteen known compounds 2-17 were isolated from M. alba twigs and their structures were identified by interpretation of the corresponding ESI-MS and NMR spectral data. In the tyrosinase inhibitory test, the compounds steppogenin (IC 50 0.98 ± 0.01 µM), 2,4,2 ,4 -tetrahydroxychalcone (IC 50 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…Figure 4 shows the structures of the most potent inhibitors with the corresponding IC 50 values against mushroom tyrosinase. Among the different subclasses, the highest activity has been determined for chalcones, with 2,2 ,4,4'-tetrahydroxychalcone exhibiting a very low IC50 value (0.07 µM) [51]. A significant melanogenesis inhibition potential has been reported also for galangin (IC 50 = 3.55 µM) [52], isoliquiritigenin (IC 50 = 4.85 µM) [53], kaempferol (IC 50 = 5.5 µM) [54], and dihydromorin (IC 50 = 9.4 µM) [55], belonging to different flavonoid subfamilies, but all characterized by at least one resorcinol moiety.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Figure 4 shows the structures of the most potent inhibitors with the corresponding IC 50 values against mushroom tyrosinase. Among the different subclasses, the highest activity has been determined for chalcones, with 2,2 ,4,4'-tetrahydroxychalcone exhibiting a very low IC50 value (0.07 µM) [51]. A significant melanogenesis inhibition potential has been reported also for galangin (IC 50 = 3.55 µM) [52], isoliquiritigenin (IC 50 = 4.85 µM) [53], kaempferol (IC 50 = 5.5 µM) [54], and dihydromorin (IC 50 = 9.4 µM) [55], belonging to different flavonoid subfamilies, but all characterized by at least one resorcinol moiety.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Agents or products that inhibit tyrosinase activity have been used in skin whitening cosmetics. Hydroquinone, arbutin, kojic acid, azelaic acid and L-ascorbic acid have tyrosinase inhibition as skin whitening agents [22][23][24]. In this study, we found that n-hexane extraction and compression of the seed has tyrosinase inhibition.…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, nine compounds were isolated from the MeOH extract of M. alba ( Figure 1 ). The structures of the compounds were determined by various spectroscopic methods, including 1D and 2D nuclear magnetic resonance to give aesculetin ( 1 ) [ 12 ], scopoletin ( 2 ) [ 13 ], scopoline ( 3 ) [ 14 ], moracin B ( 4 ) [ 15 ], moracin J ( 5 ) [ 16 ], moracin M ( 6 ) [ 17 ], moracin M 3’- O - β -glucopyranoside ( 7 ) [ 18 ], moracin M 6- β -D-glucopyranoside ( 8 ) [ 19 ], and mulberroside F ( 9 ) [ 20 ] (See Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%